Pembelajaran Lompat Jangkit Berbasis Permainan untuk Meningkatkan Motivasi Belajar Siswa SMA - Desis Mayka Rachim; Abdul Rachman Syam Tuasikal; Mochamad Ridwan (Jurnal Keolahragaan, 2026)
High  school  athletics  instruction,  especially  for  the  triple  jump,  is  often  seen  as  dull  and  repetitive  because  it  usually  focuses  only  on  technique.  Student  motivation  and  participation  levels  can  be  negatively  affected  by  this  condition..  This  study  examined  whether  a  game-based  learning  model  for  the  triple  jump  could  boost  students'  motivation  at  SMAN  1  Purwoasri.  This study used a quantitative quasi-experimental approach, with 65 eleventh-grade students selected using the cluster random sampling technique.  Researchers  collected  data  with  a  reliable  and  valid  Likert-scale  questionnaire  on  learning  motivation.  The  analytical  procedure  comprised  descriptive  data  analysis,  evaluation  of  normality  and  homogeneity  assumptions,  and  hypothesis  testing  through  an  independent-samples  t-test  based  on  the  N-Gain  scores.  The  findings  indicated  that  the  improvement  in  learning  motivation  differed  significantly  Significant differences (p < 0.05) were observed between the experimental and control groups.Students  who  learned  through  the  game-based  model  showed  greater  improvement  and  became  more  active  and  enthusiastic.  Overall,  the findings offer evidence that  the  implementation  of  a  game-based  triple  jump  learning  model  represents  an  effective  strategy  for  strengthening  learning  motivation  among  high  school  students.